Foundational theology - Ormerod, Neil; Jacobs-Vandegeer, Christiaan (Fortress Press, 2015)
Fundamental theology is traditionally viewed as the starting point for the various disciplines within Catholic theology; it is the place where solid foundations are established for the further research and engagement with the vast terrain of historical, systematic, philosophical, and sacramental/liturgical theology. In Foundational Theology, a landmark new study, Neil Ormerod and Christiaan Jacobs-Vandegeer seek to ground foundational theology in the normative drive toward meaning, truth, goodness, and beauty, appropriated by the theologian through religious, moral, intellectual, and psychic conversions. In doing so, the work maps out the implications of those fundamental orientations to the specific questions and topics of the Catholic theological tradition: God, Trinity, revelation, and an array of doctrinal points of investigation. The authors in this work provide a comprehensive approach to theological foundations for theologians while employing a new, groundbreaking approach to the discipline through the application of the insights of Bernard Lonergan, one of the foremost Catholic theologians of the modern era.